About the reconceptualization movement - Alayón-Fernández, Norberto; Molina-Molina, María Lorena (Prospectiva. Revista de Trabajo Social e Intervención Social, 2004)
This article presents the análisis about the main influences that the “movimiento de Reconceptualización” in Latin América had received. Moreover, it to sets up the contributions and the restrictions of this process; for this it rescues the critic compression coreo f a new type of social work. All of this was linking with the strategic interests of the vulnerable population. In adition, it argues about the important interrelationship between Social Work and the human rights and the present challenges for the academia formation in this yield.